2014
DOI: 10.1002/app.40747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the processing parameters and composition on the thermal stability of PLA/nanoclay bio‐nanocomposites

Abstract: Poly(lactic acid) (PLA) is one the most promising bio-based and biodegradable polymer. However, its low thermal stability limits the range of applications and complicates its transformation via the most industrial common processes. The novelty of this work is studying the thermal stability of PLA and PLA/clay nanocomposites during use, as a function of the composition and using a wide range of extrusion and injection moulding processing parameters. To improve the thermal stability of the PLA, laminar silicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
3
26
1
1
Order By: Relevance
“…Considering the nanoflake morphology of the particles, it is clear that the obtained d cp values (measured as the minimum Feret diameter) cannot be correct. In fact, those values are much higher than the ones measured using X‐ray . Still, the tomography‐based thickness values can be used to compare both nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the nanoflake morphology of the particles, it is clear that the obtained d cp values (measured as the minimum Feret diameter) cannot be correct. In fact, those values are much higher than the ones measured using X‐ray . Still, the tomography‐based thickness values can be used to compare both nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from this analysis are shown in Table . As a reference, the results for processed PLA (same conditions as the nanocomposites) are included …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For examples, clay is often used to improve the performance of PLLA. Maider et al reported the use of clay could increase the thermal stability of PLLA/nanoclay nanocomposites, and decreased the degradation rate during processing [4]. Cele et al [5] also used clay to investigate the effect of nanoclay on optical properties of PLLA/clay films.…”
Section: Introductionmentioning
confidence: 99%